Low Temperature Growth of Vertically Aligned Carbon Nanotubes by Spray Pyrolysis Method - Mageswari, S.; Syed Shabudeen, P.S.; Karthikeyan, S. (Asian Journal of Chemistry, 2015)
The aligned carbon nanotubes (ACNTs) have been synthesized using ferrocene as catalyst on silicon substrate from Rosmarinus officinalis oil as a carbon precursor at 650 °C by spray pyrolysis method in argon atmosphere. The ferrocene act an in situ Fe catalyst particle for the formation of vertically aligned CNTs on silicon substrate. The grown aligned CNTs were characterized by using HR-SEM, HR-TEM, XRD and Raman spectroscopy analysis. The average diameter of aligned CNTs was around 20nm. The advantage of this method is simple and use of low cost precursors to produce high purity aligned CNTs.